Developing Thematic Magazine Based on Character Value to Increase Honesty of Third Grade Student - Sufiani, Maulida; Haryanto, Haryanto (KnE Social Sciences, 2019)
Producing thematic magazines based on character values as learning resources to improve honesty and discipline character in third grade elementary school students is the purpose of this study. This type of research is the study of R & D by adapting procedures Borg & Gall development. The data were collected through interviews and observations, using product validation, teacher and student response questionnaire, and observation guide. The product developed was validated by media experts and material experts and then assessed by class teachers and students. The data were analyzed using the independent sample t-test dan paired sample t-test at the significance level of 0,05. This study produced a thematic magazine that was feasible, in accordance with the results of validation by media experts it was in a very good category with the total scores of 116 and 166 respectively, and according to the teachers and students, it was also in a very good category with the scores of 71 and 1799, respectively. Meanwhile, the effectiveness of the use of thematic magazines as a companion learning resource in improving honesty character is an increase and a significant difference between the control class and the experimental class after the treatment. Evidenced by the results of p <0.05, which means that there is a significant difference in effectiveness for honesty characters between the control class and the experimental class. Keywords: character, honesty, magazine, values